Penjualan Dengan Harga yang Terjangkau Guna Meningkatkan Daya Saing UMKM Dimsum Senopati - Chika Wulandari; Shirley Anggita Rahayu; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this research is to study the production process and marketing strategies carried out by the Dim Sum Senopati company and to increase our knowledge in the business sector. The method of writing this article is a descriptive method and data collection techniques through interviews, observation and documentation. And data analysis techniques using content analysis (documentation research) and descriptive analysis. The use of an affordable price strategy in selling Dim Sum Senopati is an effective step to increase business competitiveness. Competitiveness is very important in the business world in facing strong competition in the market. By offering products at affordable prices, businesses can attract more potential customers who may previously have thought products were too expensive. For this reason, companies must always try to produce high quality products but at prices that are still affordable by consumers.